2005
DOI: 10.1177/0272431604272461
|View full text |Cite
|
Sign up to set email alerts
|

Positive Youth Development, Participation in Community Youth Development Programs, and Community Contributions of Fifth-Grade Adolescents

Abstract: The 4-H Study of Positive Youth Development (PYD), a longitudinal investigation of a diverse sample of 1,700 fifth graders and 1,117 of their parents, tests developmental contextual ideas linking PYD, youth contributions, and participation in community youth development (YD) programs, representing a key ecological asset. Using data from Wave 1 of the study, structural equation modeling procedures provided evidence for five first-order latent factors representing the "Five Cs" of PYD (competence, confidence, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
1,245
8
81

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 1,159 publications
(1,366 citation statements)
references
References 73 publications
32
1,245
8
81
Order By: Relevance
“…The average of the five scales represents the PYD score. Scores for PYD have been found to be inversely related to the scores for depression indexed by the Center for Epidemiological Studies Depression measure (Radloff, 1977), both within a given grade level (eg fifth grade; Lerner et al, 2005) and across grades (from 5th grade to 6th grade; Gestsdottir and Lerner, 2007;Jelicic et al, 2007). Similarly, in these same reports, scores for PYD are inversely related to indices of smoking, bullying, and drug use Gestsdottir and Lerner, 2007;Jelicic et al, 2007).…”
Section: Assessment Of General Intelligence and Pydmentioning
confidence: 93%
“…The average of the five scales represents the PYD score. Scores for PYD have been found to be inversely related to the scores for depression indexed by the Center for Epidemiological Studies Depression measure (Radloff, 1977), both within a given grade level (eg fifth grade; Lerner et al, 2005) and across grades (from 5th grade to 6th grade; Gestsdottir and Lerner, 2007;Jelicic et al, 2007). Similarly, in these same reports, scores for PYD are inversely related to indices of smoking, bullying, and drug use Gestsdottir and Lerner, 2007;Jelicic et al, 2007).…”
Section: Assessment Of General Intelligence and Pydmentioning
confidence: 93%
“…Note: Derived from Lerner et al (2005b) and Roth and Brooks-Gunn (2003a) a fundamental strength of human development, the hypothesis was generated that, if the strengths of youth (e.g., as represented by the S, O, and C components of intentional self regulation; Freund and Baltes 2002;Gestsdóttir and Lerner 2008) are aligned with resources for healthy growth present in the key contexts of adolescent development-the home, the school, and the communitythen enhancements in positive functioning at any one point in time (i.e., well-being; Lerner 2004) will be more likely to occur; in turn, the systematic promotion of positive development (i.e., thriving; e.g., Lerner 2004;Lerner et al 2005a, b) will occur across time. A key subsidiary hypothesis is that there exist, across the key settings of youth development (i.e., families, schools, and communities) ''developmental assets'' , that is, features of the ecology of human development that support the growth of a healthy youth.…”
Section: Charactermentioning
confidence: 99%
“…The study sought to examine the strengths of diverse youth within the multitude of settings in which they are embedded; many, but not all, youth were engaged in a variety of out-of-school-time (OST) activities, but, again, the great majority of youth were not engaged in 4-H programs. The findings from the study have been reported in several special issues of journals (Lerner et al 2005, special sections of journals , and in numerous single articles, chapters, and books (see Lerner et al 2013; in press, for reviews). The present special issue presents empirical reports from across all waves of the study.…”
Section: Introductionmentioning
confidence: 70%
“…The full details of the method of the 4-H Study have appeared in numerous publications (e.g., Lerner et al 2005Lerner et al , 2009bLerner et al , 2010Lerner et al , 2011. Accordingly, we provide here only a summary of the overall method of the study.…”
Section: The 4-h Study Of Positive Youth Development (Pyd)mentioning
confidence: 99%
See 1 more Smart Citation